Starved lubrication analysis of angular contact ball bearing based on a multi-degree-of-freedom tribo-dynamic model - Chengwei Wen; Xianghui Meng; Jiaming Gu; Lin Xiao; Shuang Jiang; Hanbing Bi (Friction)
Abstract When the oil supply is not adequate to maintain the ideal lubrication, angular contact ball bearing will enter into the starved lubrication regime resulting in the potential performance degradation and consequently the severe failures. To study the effects of starved lubrication on the performance of angular contact ball bearing, this paper first proposes a multi-degree-of-freedom (DOF) tribo-dynamic model by introducing five-DOF inner ring, six-DOF balls, and six-DOF cage. The model considers the starved lubrication in the ball-raceway contact and the full multi-body interactions between the bearing components. With different ball-raceway starvation degrees being analyzed, the effects of starved lubrication on the bearing tribo-dynamic performance are first revealed. By comparison, it is found that the oil film thickness, the skidding performance, and the traction forces in the ball-raceway contact are significantly influenced by the starvation degrees. It is also found that the starvation-induced change of the ball-pocket contact force is dramatical under combined loads, and the maximum contact force under this load condition increases with the increasing starvation degrees.